2016
DOI: 10.1186/s13073-016-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

An expansion of rare lineage intestinal microbes characterizes rheumatoid arthritis

Abstract: BackgroundThe adaptive immune response in rheumatoid arthritis (RA) is influenced by an interaction between host genetics and environment, particularly the host microbiome. Association of the gut microbiota with various diseases has been reported, though the specific components of the microbiota that affect the host response leading to disease remain unknown. However, there is limited information on the role of gut microbiota in RA. In this study we aimed to define a microbial and metabolite profile that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
659
7
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 669 publications
(722 citation statements)
references
References 50 publications
36
659
7
20
Order By: Relevance
“…In this study, three genera, Collinsella, Eggerthella, and Faecalibacterium, were found to be associated with RA; abundance of Collinsella was strongly correlated with the production of the proinflammatory cytokine IL-17A [16]. The role of Collinsella in altering gut permeability and disease severity has been confirmed in experimental arthritis [16]. A more recent study evaluated human fecal Lactobacillus community and its relationship with RA [17].…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 62%
See 3 more Smart Citations
“…In this study, three genera, Collinsella, Eggerthella, and Faecalibacterium, were found to be associated with RA; abundance of Collinsella was strongly correlated with the production of the proinflammatory cytokine IL-17A [16]. The role of Collinsella in altering gut permeability and disease severity has been confirmed in experimental arthritis [16]. A more recent study evaluated human fecal Lactobacillus community and its relationship with RA [17].…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 62%
“…On the one hand, there is much evidence that supports the association between RA and the intestinal microbiota; bacteria such as Mycoplasma fermentans [12], Escherichia coli [13], and Proteus mirabilis [14] have been reported to initiate the disease. On the other hand, it has been demonstrated that gastrointestinal and urogenital infections are associated with a significantly lowered risk of RA [15] and that patients with RA exhibit decreased gut microbial diversity compared with controls [16]. In particular, it has been proved that expansion of rare taxa such as Actinobacteria along with decrease in abundant taxa occur in patients with RA compared with controls [16].…”
Section: Gastrointestinal Microbiota In Rheumatoid Arthritis Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was the case for instance in obesity, COPD, pancreatitis, chronic inflammatory arthritis and non alcoholic fatty liver disease (NAFLD) [53][54][55][56][57]. In this last disease, the presence of selected bacterial DNA, identified through gut MWAS, was retrieved in patient blood samples and is a way to get a simple and less invasive disease biomarker to replace liver biopsies [58].…”
Section: Metagenomic Analysismentioning
confidence: 99%